2007
DOI: 10.2190/om.55.3.c
|View full text |Cite
|
Sign up to set email alerts
|

The Fundamental Paradox in the Grief Literature: A Critical Reflection

Abstract: A key theme in the bereavement literature is the recognition that every grief experience is unique and dependent on many variables, such as the circumstances of the death, characteristics of the bereaved individual, their relationship with the deceased, the provision and availability of support, and a myriad of sociocultural factors. Concurrently, there are corresponding efforts to define "normal" grief and delineate it from "complicated" grief experiences. The discord between these two potentially opposing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 88 publications
3
88
0
3
Order By: Relevance
“…Overwhelmingly, the participants were clearly not complicit with the pervasive conceptualisations that construct grief narrowly as a stage-based and short-term phenomenon with pathological variants (Breen & O'Connor, 2007;CAH, 2004;Rothaupt & Becker, 2007;Wortman & Boerner, 2007). Instead, they favoured a partnership model of support where they are presented with alternatives and are able to control decision-making processes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Overwhelmingly, the participants were clearly not complicit with the pervasive conceptualisations that construct grief narrowly as a stage-based and short-term phenomenon with pathological variants (Breen & O'Connor, 2007;CAH, 2004;Rothaupt & Becker, 2007;Wortman & Boerner, 2007). Instead, they favoured a partnership model of support where they are presented with alternatives and are able to control decision-making processes.…”
Section: Resultsmentioning
confidence: 95%
“…and 'psychologised' lenses, which has resulted in the articulation and proliferation of a pervasive dominant grief discourse (Breen & O'Connor, 2007;Rothaup & Becker, 2007;Small & Hockey, 2001). In this paper we have attempted to show that, throughout the grief experience following the death of a loved one in a crash, the dominant grief discourse is privileged while the experiences of the bereaved are silenced.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore while there have been studies documenting the experience of grief (e.g. Arnold, Buschman Gemma, & Cushman, 2005), there appears a dearth of research on how individuals subjectively experience grief therapy (Breen & O’Connor, 2007). …”
mentioning
confidence: 99%
“…The notion of anticipatory grief is accepted by many end-of-life practitioners, despite its theoretical and empirical challenges. 24,25 Currently, empirical evidence is equivocal. A pioneering review of the literature on bereavement and caregiving indicated that family caregivers adjusted relatively well to the death of the person for whom they were caring.…”
Section: Limitations To Current Understandings Of Caring and Bereavementmentioning
confidence: 99%